2015
DOI: 10.1111/papt.12069
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome of an Internet‐based cognitive‐behavioural therapy for post‐traumatic stress disorder in older adults

Abstract: Greater internal locus of control and post-traumatic growth is associated with greater improvement in PTSD symptoms following Internet-based CBT. Older adults with initial high internal locus of control and post-traumatic growth, respectively, did not differ with respect to initial PTSD severity, but they showed a more pronounced response to treatment. It could be assumed that patients with initial functional appraisals could benefit easier and faster from a trauma-focused cognitive-behavioural therapy compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 50 publications
3
6
0
2
Order By: Relevance
“…The results showed that group training of trauma-Focused cognitivebehavioural therapy has been effective in reducing the depression symptoms of the experimental group in posttest and follow-up stages. The findings of this study were in line with the studies of Fakhary et al, 17 bottche et al, 21 Wamser-Nanney et al, 18 Del Palacio-Gonzalez et al, 22 Rodriguez-Rey et al, 23 Cohen et al 15 muris et al, 24 which…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that group training of trauma-Focused cognitivebehavioural therapy has been effective in reducing the depression symptoms of the experimental group in posttest and follow-up stages. The findings of this study were in line with the studies of Fakhary et al, 17 bottche et al, 21 Wamser-Nanney et al, 18 Del Palacio-Gonzalez et al, 22 Rodriguez-Rey et al, 23 Cohen et al 15 muris et al, 24 which…”
Section: Discussionsupporting
confidence: 91%
“…Individuals with symptoms of PTSD or other mental health problems may be less likely to engage in treatment approaches premised on the individual as the agent of change, including cognitive behavioural therapy (CBT), if they hold a strong belief that they were destined to have these problems. Indeed, in a recent paper looking at predictors of outcome following internet based CBT for treatment of PTSD in older patients, it was noted that patients with greater internal locus of control demonstrated a better response to treatment [33]. Give that trauma-focused CBT is considered best practice in the treatment of PTSD [34] and is widely used by Western-based clinicians, further understanding of the relationship between such beliefs and the concept of locus of control would offer useful insights to assist in the development of mental health treatment programs for refugees.…”
Section: Discussionmentioning
confidence: 99%
“…Des Weiteren konnte Trösken [2] Zusammenhänge zwischen Ressourcenkonstrukten und allgemeinen Indikatoren für den Therapieerfolg nachweisen. Was den Einfluss von Ressourcen auf den Behandlungs erfolg bei Depressionen oder posttraumatischen Belastungsstörung (PTBS) betrifft, hat es unseres Wissens nach bislang nur eine Studie mit einer internetbasierten Intervention gegeben [14].…”
Section: Introductionunclassified
“…Es ist jedoch auch gut möglich, dass man mit spezifischeren Ressourcenkonstrukten wie z. B. internalen Kontrollüberzeugungen wie in der Studie von Böttche et al[14] durchaus Effekte von Ressourcen hätten feststellen können. Hierzu wäre es allerdings notwendig gewesen diese Konstrukte mit den einschlägigen Messinstrumenten reliabel zu erfassen und nicht wie es in unserer Stu-die der Fall gewesen ist, einen globalen Wert für die Ausstattung einer Person mit sozialen und personalen Ressourcen heranzuziehen.…”
unclassified